Invasive epithelial ovarian carcinoma (EOC) at a young age: role of fertility-sparing - Puja Agung Antonius; Tricia Dewi Anggraeni (Jurnal Ilmu Kesehatan Indonesia, 2022)
Objective: Improving knowledge to manage an invasive epithelial ovarian cancer at a young age who expect to preserve their reproductive function Method: a Case report Result : A 26 years old, nulliparity, Indonesian woman with chief complaint abdominal enlargement simultaneous with dyspnoea condition. Physical examination revealed an enlarged abdomen until processus xhypoideus with positive shifting dullness. Gynecology examination found normal uterine size, palpable cystic mass originated from adnexa until navel, mobile. CT whole abdomen showed a cystic solid mass in the pelvic area up to mid abdominal size 17,8 x 10,7 x 18,8 cm accompanied by lymphadenopathy in paraaortic and bilateral inguinal. Ascites and pleural fluid cytology examination results were both positive for malignant cells (metastatic adenocarcinoma). The patient was assessed as advanced staged ovarian cancer and procced for Interval Debulking Surgery (IDS) after 3 cycles of Neoadjuvant Chemotherapy (NACT). Postoperative histopathology examination result was high-grade clear cell ovarian carcinoma Conclusion: Fertility-sparing surgery for invasive epithelial ovarian carcinoma could be chosen for selective young age patients who fulfilled the criteria. Education and informed consent is a must regarding the risk of recurrence and prognosis. Keywords: Invasive EOC, fertility sparing, selection criteria, recurrence, prognosis